The Function, Regulation and Mechanism of Programmed Cell Death of Macrophages in Atherosclerosis - Liu, Chang; Jiang, Zecheng; Pan, Zhongjie; Yang, Liang (Frontiers in Cell and Developmental Biology, 2022)
Atherosclerosis is a chronic progressive inflammatory vascular disease, which is an important pathological basis for inducing a variety of cardio-cerebrovascular diseases. As a kind of inflammatory cells, macrophages participate in the whole process of atherosclerosis and are the most abundant immune cells in atherosclerotic plaques. Recent studies have shown that programmed cell death plays a critical role in the progression of many diseases. At present, it is generally believed that the programmed death of macrophages can affect the development and stability of atherosclerotic vulnerable plaques, and the intervention of macrophage death may become the target of atherosclerotic therapy. This article reviews the role of macrophage programmed cell death in the progression of atherosclerosis and the latest therapeutic strategies targeting macrophage death within plaques.